Implementing Class Wide Peer Tutoring to Enhance Students' Mathematical Reasoning Ability in Understanding Absolute Value Equations and Inequalities - Gradini, Ega; B, Firmansyah; Wahyuni, Septia; Mailinda, Meri (Journal of Medives : Journal of Mathematics Education IKIP Veteran Semarang; Vol 5 No 1 (2021): Journal of Medives : Journal of Mathematics Education IKIP Veteran SemarangDO - 10.31331/medivesveteran.v5i1.1238, 2021)
This article aims to determine the effectiveness of Class Wide Peer Tutoring (CWPT) implementation to improve students' mathematical reasoning abilities. This research is experimental research with a mixed-method approach. The research sample was determined through cluster random sampling. Data were collected through mathematical reasoning tests arranged according to indicators of mathematical reasoning ability. Data were analyzed using inferential statistics with the stages of normality, homogeneity, and hypothesis testing. The result shows that the implementation of CWPT enhances students' mathematical reasoning on Equations and Inequalities of an Absolute Value. Mathematical reasoning test results show that the 10 th grader score of mathematical reasoning is 76.75 (Good). The indicator of mathematical reasoning that is the most difficult for students to master is "drawing logical conclusions" with the acquisition of a mathematical reasoning score of 35.81 (poor), while the easiest mastered by students is "Presenting mathematical statements or premises in writing, drawings or graphics" with mathematical reasoning score of 80.14 (Very Good). The students' mathematical reasoning ability on the indicator "compiling an analogy or explanation of the problem and its solution" is 74.09 (Good). The mathematical reasoning ability of students on the indicator "mathematical manipulation" is 42.10 (fair). Keywords: Mathematical Reasoning, Students’ ability, Class Wide Peer Tutoring